Stereotip Gender terhadap Perempuan dalam Novel Perempuan yang Menangis kepada Bulan Hitam Karya Dian Purnomo - Fanny Oktiza; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This article aims to describe:(1) the forms of gender stereotypes for women in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, (2) the causes of gender stereotypes for women in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo, and (3) the impact of gender stereotypes on women in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. The type of research used is literary research with descriptive methods. The data source used in this study is the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. Based on the research conducted, it was found that there were 6 forms of labeling attached to women in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. The stereotypes that are attached are, women are week, women are emotional, women are motherhood, women are managing household affairs, women are serving husband, and women are sex objects. Factors that cause gender stereotypes for women are social factors, and cultural factors. The impact of gender stereotypes on women is subordination, marginalization, violence and harassment, and workload.